Determining of Social-Cultural, Environmental and Economic Impacts of Winter European Youth Olympic Festival - Yaprakli, Tevfik Sukru; Unalan, Musa (Sosyoekonomi Soc, 2020)
In this study, we try to determine the effects of social-cultural, environmental and economic impacts as well as the perceived success of the organizational committee of the Winter European Youth Olympic Festival (EYOF) on the public support to the organization. The research utilizes survey method and employs data collected from 500 participants in Erzurum Province of Turkey to test the research hypotheses. The collected data is analyzed by SPSS 22 software package through arithmetic mean, standard deviation, frequency distribution and regression analysis. The findings of the study show that perceived success of EYOF Committee have a significant effect on perceived positive social-cultural impacts, environmental impacts, economic impacts and perceived negative social-cultural impacts and economic impacts. The fmdings also indicate that perceived positive economic impacts, perceived negative environmental impacts and perceived success of EYOF Committee has a significant effect on local community's support to EYOF.
Keywords: EYOF; Social-Cultural; Environmental; Economic Impacts